An Answer to a Question by Wilf on Packing Distinct Patterns in a Permutation - Coleman, Micah (The Electronic Journal of Combinatorics, 2004)
We present a class of permutations for which the number of distinctly ordered subsequences of each permutation approaches an almost optimal value as the length of the permutation grows to infinity.